Teachers Efforts in Maintaining Student Religiosity at Madrasah Aliyah Unggulan KH. Abd. Wahab Hasbullah Bahrul Ulum Tambakberas, Jombang, East Java (2020-2021) - Noor Syahid; Ira Awalin Nafiah (Prodi Pendidikan Agama Islam, Fakultas Tarbiyah, Universitas Darussalam Gontor, 2021)
The teacher a person which will responsible to develop their student by pursuing all his potentials: cognitive potential, affective potential, and psychomotor. Teacher's effort is what teachers do as professional educators in educating, guiding, directing, and evaluating learners by developing all the potentials that exist in the learner. Therefore, all teachers in Madrasah Aliyah Unggulan KH. Abd. Wahab Hasbullah Bahrul Ulum Tambakberas (MAUWH), Jombang strives to maintain the religiosity of students at school and at home, as well as continue to develop the talents possessed by students by providing the necessary facilities. This research is qualitative research with educational psychology approach. To obtain the required data, researchers used three methods, namely: 1) interview method, 2) observation method, 3) documentation method, and in analysing the data, researchers used interactive analysis of Miles and Huberman models with data reduction, data study, and draw conclusion. Based on data analysis, researchers concluded: a) teachers effort in maintaining student religiosity at MAUWH can be seen from four aspects, namely: 1) aspects of civility, 2) aspects of habituation, 3) aspects of talent development, and 4) aspects of motivation. These efforts are carried out in class learning situations, daily activities in schools, talent development that is still appropriate in the values of Pondok Pesantren Bahrul Ulum based on religiosity. Then the supporting factor and inhibition of teachers' efforts in maintaining student religiosity at MAUWH are as follows. b) Supporting factors include students' interest in learning activities in a subject, teacher interest in skilled subjects, teacher love for Islamic religious education, well-available learning strategies and media, activeness of students and teachers in madrasahs, and good evaluation methods to improve learning activities and outcomes in MAUWH. And c) the inhibition factor is limitations of existing facilities, especially in matters related to digital IT, differences in understanding or intelligence of learners.